2020
DOI: 10.1136/esmoopen-2019-000662
|View full text |Cite
|
Sign up to set email alerts
|

ESMO Clinical Research Observatory (ECRO): improving the efficiency of clinical research through rationalisation of bureaucracy

Abstract: acknowledgements We are indebted to Klizia Marinoni for her support in coordinating the activities of the group; and to Paul Miller for revising the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…To be precise, in recent years, the delegation of many activities like trial set-up and monitoring through CROs not only added another layer of complexity between investigators and sponsors, but also added a number of extra-requirements which significantly increased the level of operational burden [4]. Although patients' safety remains the utmost priority, the GCP principles did not change significantly since the Declaration of Helsinki in 1964, but in contrast, an exponential increase affecting trial set-up efforts, trial execution procedures, data recording, monitoring and auditing has been observed [5,6].…”
mentioning
confidence: 99%
“…To be precise, in recent years, the delegation of many activities like trial set-up and monitoring through CROs not only added another layer of complexity between investigators and sponsors, but also added a number of extra-requirements which significantly increased the level of operational burden [4]. Although patients' safety remains the utmost priority, the GCP principles did not change significantly since the Declaration of Helsinki in 1964, but in contrast, an exponential increase affecting trial set-up efforts, trial execution procedures, data recording, monitoring and auditing has been observed [5,6].…”
mentioning
confidence: 99%
“…Regulators, such as the US Food and Drug Administration 41 ; health systems, like the United Kingdom National Health Service 42 ; professional oncology societies, such as the European Society of Medical Oncology and the American Society of Clinical Oncology 30 , 43 ; academicians; and industry should continue to make efforts to streamline clinical research and reduce the burden of paperwork. 44 It is a challenge for principal investigators to sign off and act as guarantor for electronic case record forms and multiple serious adverse event reports; it is important that investigator oversight is not diluted by collecting ever-increasing volumes of data for which they are not easily equipped to vouch and certify.…”
Section: Increased Use Of Technologymentioning
confidence: 99%
“…Even before the COVID-19 pandemic, important barriers impacted on the conduct of clinical trials ( 18 , 19 , 20 ). Different research groups have been proposing a number of solutions in order to remedy the complex, and at times dysfunctional reality of clinical cancer research ( 19 , 20 , 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Even before the COVID-19 pandemic, important barriers impacted on the conduct of clinical trials ( 18 , 19 , 20 ). Different research groups have been proposing a number of solutions in order to remedy the complex, and at times dysfunctional reality of clinical cancer research ( 19 , 20 , 21 , 22 ). To add to this background, clinical research activities were seriously impaired at the beginning of the SARS-CoV-2 pandemic resulting in many sites struggling to maintain their trial activity and to start new studies ( 18 , 23 , 24 , 25 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation